Cross-sectional survey of attitudes and beliefs about back pain in New Zealand. Issue 5 (23rd May 2014) - Darlow, Ben; Perry, Meredith; Stanley, James; Mathieson, Fiona; Melloh, Markus; Baxter, G David; Dowell, Anthony
Abstract : Objectives: To explore the prevalence of attitudes and beliefs about back pain in New Zealand and compare certain beliefs based on back pain history or health professional exposure. Design: Population-based cross-sectional survey. Setting: Postal survey. Participants: New Zealand residents and citizens aged 18 years and above. 1000 participants were randomly selected from the New Zealand Electoral Roll. Participants listed on the Electoral Roll with an overseas postal address were excluded. 602 valid responses were received. Measures: Attitudes and beliefs about back pain were measured with the Back Pain Attitudes Questionnaire (Back-PAQ). The interaction between attitudes and beliefs and (1) back pain experience and (2) health professional exposure was investigated. Results: The lifetime prevalence of back pain was reported as 87% (95% CI 84% to 90%), and the point prevalence as 27% (95% CI 24% to 31%). Negative views about the back and back pain were prevalent, in particular the need to protect the back to prevent injury. People with current back pain had more negative overall scores, particularly related to back pain prognosis. There was uncertainty about links between pain and injury and appropriate physical activity levels during an episode of back pain. Respondents had more positive views about activity if they had consulted a health professional about back pain. The beliefs of New Zealanders appeared to be broadly similar to those of other Western populations. Conclusions: A large proportion of respondents believed that they needed to protect their back to prevent injury; we theorise that this belief may result in reduced confidence to use the back and contribute to fear avoidance. Uncertainty regarding what is a safe level of activity during an episode of back pain may limit participation. People experiencing back pain may benefit from more targeted information about the positive prognosis. The provision of clear guidance about levels of activity may enable confident participation in an active recovery.